Characteristics of chaotic pulse trains generated by Lightning flashes - Gomes, C.; Cooray, V.; Fernando, I.M.K.; Montano, R.; Sonnadara, D.U.J. (My University, 2004)
Pulse trains of irregular pulse characteristics and erratic amplitudes are observed in lightning flashes. These are termed ‘‘chaotic pulse trains’’ in this study. The average width of the individual pulses of these pulse trains is in the range of a few microseconds, with the lower limit of individual measurements extending into the sub-microsecond region. The typical pulse separation lies in the range of 2–20 ms: The pulse duration shows a consistent distribution with the most probable value at 400–500 ms: Chaotic pulse trains occur most often immediately prior to subsequent strokes. However, they occur also a few milliseconds to several tens of milliseconds prior to return strokes and sometimes do not precede return strokes at all. Twenty-six percent of the total subsequent strokes recorded in this study were preceded by chaotic pulse trains. A few of these pulse trains have occurred in a sequence of several tens of millisecond intervals in between return strokes. We have also found them to occur within very intense cloud flashes. These chaotic pulse trains have features that are different from those of other known pulse trains reported in the lightning literature. Hence, they may be caused by a physical process that has not yet been identified.
Keywords: Characteristics; chaotic pulse trains; lightning; flashes